Empowering Millennial Farmers To Improve The Competitiveness Of Agricultural Products In Domestic And Global Markets - Gulo, Niscaya; Septiana Galdistia Nabila; Cakti Indra Gunawan (International Research & Development for Human Beings (IRDH), 2024)
The purpose of this study is to determine the importance of the role of millennial farmers as a new generation that can bring innovation, technology and entrepreneurial spirit to the world of agriculture. This research method uses qualitative descriptive analysis with literary comparison, namely comparing various literature sources such as scientific journals, books, and relevant articles to explore the perspectives and practices of empowering millennial farmers. The results show that the success of empowering millennial farmers is greatly influenced by the active involvement of the younger generation in agricultural innovation. Millennial farmers are identified as an important group that brings innovative roles, digital technology, and entrepreneurial spirit to the world of agriculture, thereby increasing the competitiveness of agricultural products in domestic and international markets.